Arthropathy of Down syndrome: an under-diagnosed inflammatory joint disease that warrants a name change - Orla G Killeen; Charlene M Foley; Derek A Deely; Emma Jane MacDermott (RMD Open)
Objective To identify undiagnosed cases of A-DS and document time to diagnosis. Also to describe clinical, laboratory and radiological features of A-DS at diagnosis.Methodology Children with Down syndrome (DS) (0–21 years) were invited to attend a musculoskeletal screening clinic. A second physician at a further clinic confirmed suspected cases of A-DS. Investigations and treatment were instigated as per normal clinical practice for Juvenile idiopathic arthritis (JIA). Data on a convenience sample of 21 newly diagnosed children with JIA was collected to create a comparison group.Results Over an 18-month period, 503 children with DS were screened for arthritis and 18 new cases diagnosed. In total, 33 children were identified with A-DS (combining cases attending pre-dating commencement of the study and those referred to our centre during the study period). This suggests prevalence of A-DS is 20/1000. A significant delay in diagnosis of A-DS was observed. The majority of children presented with polyarticular-rheumatoid factor-negative arthritis, with predominance in the small joints of the hands and wrists. Erosive changes were reported on X-ray in a significantly greater proportion (42%) of children with A-DS than JIA (14%). MRI was used to confirm diagnosis in four cases.Conclusion Children with DS are at increased risk of arthritis. Future research to accurately define disease pathogenesis and identify a biomarker of disease would be of benefit.